Advancements in Algal Biofuels Research - Recent Evaluation of Algal Biomass Production and Conversion Methods of into Fuels and High Value Co-products - S. Kent Hoekman (Frontiers Research Topics, 2017)
Algae biomass has enormous potential to produce fuels and value-added products. Algae-derived biofuels and bioproducts offer great promise in contributing to U.S. energy security and in mitigating the environmental concerns associated with conventional fuels. Algae's ability to grow in low quality water/wastewater and to accumulate lipids has encouraged scientists to investigate algae as a medium for wastewater treatment and a potential source of fuel and bioproducts. There are growing demands for biomass-based transportation fuels, including biodiesel, bio-oil, biomethane, biohydrogen, and other high-value products (nutraceuticals, proteins, omega-3 etc.). Algae can help address these needs. The topic of algae energy includes the production and characterization of algae cultures, conversion into fuel feedstocks and high value products, and optimization of product isolation and use. In view of the increasing efforts in algae biomass production and conversion into energy and high-value products, the current research topic covers important aspects of algal strain selection, culture systems, inorganic carbon utilization, lipid metabolism and quality, biomass harvesting, extraction of lipids and proteins, and thermochemical conversion of algal feedstocks into biocrude.